Nitrogen concentrations and nitrogen isotopic compositions in leaves of Cinnamomum Camphora and Pinus massoniana (Lamb.) for indicating atmospheric nitrogen deposition in Guiyang (SW China). (June 2017) - Xu, Yu; Xiao, Huayun; Qu, Linglu
Abstract: Nitrogen (N) concentrations and δ 15 N signatures in soil and camphor ( Cinnamomum Camphora ) and Masson pine ( Pinus massoniana Lamb.) leaves collected along an urban-rural gradient in Guiyang (SW China) were investigated systematically. N concentrations in camphor (1.01–2.37%) and Masson pine (0.99–2.42%) leaves showed a significant decrease from central Guiyang (0–6 km) to suburban areas (18–24 km), while slightly increased leaf N concentrations reemerged at areas more than 24 km from the city center. The δ 15 N values in camphor and Masson pine leaves also decreased from central Guiyang to the rural area, with more positive leaf δ 15 N in the urban area and 15 N-depleted leaf δ 15 N in the rural area. No significant differences were observed for soil N concentrations and soil δ 15 N in these areas, which suggested that the decrease in leaf N concentrations was due to decreased atmospheric N deposition along the urban-rural gradient and that there were two isotopically different atmospheric N sources in Guiyang city: foliar δ 15 N values in urban areas were mainly influenced by 15 N-enriched atmospheric NOx -N from traffic emissions, while those in rural areas were primarily affected by 15 N-depleted atmospheric NHx -N from agricultural activities. However, the pattern of moss (collected ten years prior, with lower traffic density and wastewater treatment rate in the urban area) δ 15 N variation in the urban area (0–12 km) was contrary to that of the camphor and Masson pine leaves, indicating that the δ 15 N values in previously collected urban mosses were mainly controlled by isotopically light NHx -N from untreated wastes and sewage, but were much less affected by traffic. For the trees in the urban area, N concentrations in camphor and Masson pine leaves varied in parallel with their δ 15 N values ( P < 0.0001), and we thus applied a mass balance equation to estimate the δ 15 N value (about 7‰) in the atmospheric N deposition in the urban area. This indicated that the greater δ 15 N in urban camphor and Masson pine leaves reflected a higher contribution of NOx -N to N deposition. This study shows that the analysis of N and δ 15 N in camphor and Masson pine leaves is a promising method to indicate N deposition. Highlights: N concentrations in camphor and Masson pine leaves can indicate N deposition. δ 15 N of vascular plant leaves can provide an indication of the main N sources. 15 N-enriched traffic NOx -N was the dominant atmospheric N source in urban areas. 15 N-depleted agricultural NHx-N was the main atmospheric N source in rural areas.